The Role of Innovation Activity in The Conditions of Economy Globalization (European Journal of Economics, Finance and Business Development, 2023)
This article presents the main ways in which innovation can have a positive impact on economic growth, welfare of the population, economic structure, social image of society and various sectors of the economy, innovation opportunities, their application and development prospects.